An Analytical Study of Liquidity Performance of Selected Pharmaceutical Companies in India - Sanjana Joshi (Journal of Social Commerce, 2024)
This article is an analytical study on liquidity performance of selected Indian pharmaceutical companies. The main objective of this study is to analyze the liquidity ratio and compare the liquidity performance of selected samples during the study period of 2017-18 to 2021-2022. All samples have been selected by a non-probability sampling method. This study is mainly based on secondary data and these data are collected by authentic website money control and company annual reports, furthermore hypothesis testing is done by one-way analysis of variance. The findings of this study are that all companies maintain well CR. That means all companies effectively manage their current assets against current liabilities, but Sun Pharma company has not enough quick assets to manage their short-term requirements while other companies maintain enough quick assets against short term requirements. Sun Pharma does not have enough cash retained earnings because it provides the highest dividend. That is why its dividend payout ratio is very high, while Reddy's, Devi's, and Cipla maintain a good retained earning ratio. That is why they don't provide more dividends. According to the dividend point of view, Sun Pharma is well established and the leader of its industries.